Extreme sports evaluation: Evidence from judging figure skating - Lee, J. (The economics of family and group decisions, 2004)
Chapter 4. Extreme Sports Evaluation: Evidence from Judging Figure Skating 4.1 Introduction 4.2 Conceptual Framework 4.2.1 Judging Figure Skating and Figure Skating Judges 4.2.2 Modelling Outlier Aversion Bias 4.3 Empirical Analysis 4.3.1 Data and Descriptive Statistics 4.3.2 Identi¯cation I: Dynamic Panel Data Estimation 4.3.3 Identi¯cation II: Interim Judging System 4.4 Information Loss due to Outlier Aversion 4.5 Implications